Effect of chemical modification of eggshells powder filled low density polyetylene composites - Siti Shuhadah, Md Saleh (Universiti Malaysia Perlis, 2011)
Eggshells powder filled low density polyethylene (LDPE/ESP) composites were studied. The composites were prepared by using Z-blade mixer at 1800C using a rotor speed of 50 rpm for 6 minutes. Sample of composites were compression moulded, in an electrically heated Hydraulic press. Hot press procedures involved preheating at 1800C for 4 min followed by compression for 2 min at the same temperature and subsequent cooling under pressure for 2 min. It was found that the tensile strength and elongation at break for the composites decreased with the increasing filler loading. Young’s modulus for the composites increases with the increasing filler loading. Then the composites were modified with isophthalic acid (LDPE/ESPI), ethylene diamine-co-isophthalic acid (LSPE/ESPM) and polyethylene-grafted-maleic anhydride (LDPE/ESPPEMAH). It was found that improvement in interfacial adhesion has enhanced the tensile strength and water absorption resistance of LDPE/modified eggshells powder composites compare to LDPE/unmodified eggshells powder composites (LDPE/ESP).Its also increased thermal stability and percent of crystallinity of composites. Better interfacial adhesion between LDPE and eggshells powder are responsible for the improvement of mechanical properties of LDPE/modified eggshells powder composites, as evident by scanning electron microscopy (SEM) on tensile fracture surface of the composites.